Bioefficacy of Trichoderma spp. for the management of soil borne fungal pathogens - S. BEENA, V.M. HIMA* and (Indian Phytopathology, 2016)
The present study was conducted to evaluate the antagonistic property of twenty native isolates of Trichoderma spp. isolated from different soil samples of Kerala state and to compare that with the reference culture of Trichoderma viride released by Kerala Agricultural University under in vitro and in vivo conditions. Results of the dual culture experiment against 6 soil borne fungal pathogens viz., Pythium aphanidermatum, Phytophthora capsici, Rhizoctonia solani, Sclerotium rolfsii, Ganoderma lucidum and Fusarium oxysporum f.sq. cubense revealed that antagonistic performance of all the native isolates was better than that of reference culture with respect to one or other pathogen. It was found that cellulose degrading efficacy of all isolates except Tr 2 and Tr 109 ranges from 0.5 to 1.0. In the pot experiment, disease incidence was found to be less in T1 (59.88%) followed by T7 (67.67%), T4 (74.83%) and T10 (79.9%). All these experiments revealed that the isolates viz., Tr43 (T7), Tr76 (T1), Tr9 (T4), Tr41 (T10) and Tr48 (T2) recorded the highest efficiency over the reference culture of Trichoderma viride.